The impact of Chinese investment on economic and political development in East Africa : comparative case study of Ethiopia and Kenya - Loužecký, Tomáš; Garlick, Jeremy; Veselá, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The diploma thesis is focused on the issue of the influence of Chinese investments in the period of 2013–2022 on economic and political development in the country. The main goal of the work is to compare the effects in two selected cases: Ethiopia and Kenya. For the evaluation of these effects, ten main indicators were established, which are supplemented by additional findings on the influence of Chinese investments in selected cases. These indicators are: Motive of China, Corruption, Debt, GDP growth and net welfare gains, Employment, Manufacturing, Cooperation, Regional integration, Institutions, and Political context in chosen cases. The work is divided into six chapters. The first is focused on the theoretical grounding, which is neoliberalism. Its implications for economic and political development in the country served to select the indicators. The second and third chapters discuss the context of historical ties between China and Africa and Chinese investments in Africa respectively. The fourth and fifth chapters are focused on selected cases. The chapters discuss the current political and economic status of the countries, Chinese investments there, and subsequently their impact on economic and political development. The last chapter is a comparison of these two cases. After the comparison, a more positive impact on Ethiopia was found from a political and economic point of view. Subsequently, factors were identified that connected the influence of investments in both countries.
Vedoucí práce: Jeremy Alan Garlick
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor dipl. práce]; diplomové práce; master's theses